Will China's new financial regulatory reform be enough to meet the challenges? - Martin Chorzempa; Nicolas Véron (Bruegel, 2023)
Effective financial supervision plays a crucial role in maintaining financial stability and a healthy financial system. China's leadership has made financial risk a core priority, and in reforms approved in March 2023, it reassigned regulatory responsibilities, creating a new supervisory body that will take over some responsibilities from the central bank, the banking and insurance regulator, and the securities regulator. The aim is that a change to the financial supervisory architecture (who does what in financial supervision) will make China's system more effective and stable. In this policy brief, we argue that this incremental reform will not solve the core issues China faces in financial supervisory effectiveness. We provide an overview of China's large and complex financial system, including its largely state-owned banks (some of which are the largest in the world by assets), securities markets and other financial intermediaries. Traditional divisions between different types of activities and institutions have been blurred by the rise of large financial conglomerates, risk-transfer techniques and internet-based finance. Reforms in 2018 to China's supervisory architecture did not eliminate perceived shortcomings, including failures to effectively regulate financial conglomerates, fintech and regional banks. We then survey global benchmarks against which China's financial supervisory architecture can be compared, including the United States and European Union. China's supervisory system is already more streamlined, at least on paper, than either of these most comparable global counterparts. Like them, China's system does not correspond exactly to any of the three textbook archetypes of supervision: sectoral, twin-peaks or integrated supervision. Ultimately, the effectiveness of China's financial supervisory architecture suffers from excessive state intervention in the financial system through other channels, including through the unique and pervasive influence of the communist party, which hampers supervisory independence and makes it difficult to establish accountability for regulatory failures. While the recently announced reform may improve coordination across supervisory bodies, coordination within the new quasi-integrated supervisor, across central departments, and between them and local branches, will remain a challenge.
Keywords: 330